Prognostic importance of radiologic extranodal extension in nasopharyngeal carcinoma treated in a Canadian cohort. (December 2021) - Chin, Olivia; Yu, Eugene; O'Sullivan, Brian; Su, Jie; Tellier, Anais; Siu, Lillian; Waldron, John; Kim, John; Hansen, Aaron; Hope, Andrew; Cho, John; Giuliani, Meredith; et al.
Highlights: Radiologic extranodal extension (rENE) is prognostic for nasopharyngeal carcinoma. Higher grade of rENE portends poorer distant control and survival. Inclusion of rENE in cN classification improves survival prediction. We propose dichotomizing rENE and classifying unequivocal rENE as cN3. Unequivocal rENE by stringent criteria, can be assessed reliably. Abstract: Purpose: To confirm the prognostic value of radiologic extranodal extension (rENE) and its role in clinical-N classification in nasopharyngeal carcinoma (NPC) treated in a western institution. Methods and materials: NPC treated between 2010 and 2017 were included. Pre-treatment MRI were reviewed for unequivocal rENE and its grade: grade-1: tumour invading through any nodal capsule but confined to perinodal fat; grade-2: ≥2 adjacent nodes forming a coalescent nodal mass; grade-3: tumour extending beyond perinodal fat to invade/encase adjacent structures. Overall survival (OS) and disease-free survival (DFS) were compared between rENE-positive (rENE+) and rENE-negative (rENE−) patients. Multivariable analysis (MVA) confirmed the prognostic importance of rENE and its grade. Staging schemas including rENE in N-classification were proposed and their performance evaluated. Results: A total of 274 patients were eligible (43 cN0; 231 cN-positive). rENE was identified in 83/231 (36%) cN-positive, including grade 1/2/3 rENE in 14/58/11 cases. Compared to rENE−, rENE+ patients had a lower OS (68% vs 89%, p  < 0.001) and DFS (58% vs 80%, p  < 0.001). MVA confirmed the prognostic importance of grade-2 [HR: OS: 2.85 ( p  = 0.005); DFS: 2.89 ( p  < 0.001)] and grade-3 rENE [HR: OS 5.28 ( p  = 0.004); DFS 3.86 ( p  = 0.005)], with a trend for grade-1 vs rENE− [HR: OS 2.63 ( p  = 0.13); DFS 1.49 ( p  = 0.520)]. We evaluated classifying any rENE as cN3 ( Proposal-I ) or any grade-2/grade-3 rENE as cN3 ( Proposal-II ). The stage schema with Proposal-I cN-classification ranked the highest in the performance evaluation. Conclusions: rENE is an important prognostic factor in this western NPC cohort. We propose classifying any unequivocal rENE as cN3.